A participação popular no hard case ficha limpa: estudo de sete acórdãos no TSE e do STF - Moreira, José Roberto (2012)
ABSTRACT The judicialization of politics has inspired several scientific researches due to its novelty and consequences, and formed the agenda of contemporary political science. In this context, this study sought to investigate the influence of popular participation in seven trials judged by the STF and TSE in the case "ficha limpa ( clean slate"): RO 1.069-RJ, by TSE (decided in 2006); ADPF 144-DF, by STF (decided in 2008); CC 1120-26.2010-DF, TSE (decided in 2010); RE s 630.147-DF, 631.102-PA e 633.703-MG, by STF (decided in 2010 and 2011); and joint trial of ADC s 29 and 30, and finally ADI 4578, tried by STF (decided in 2012). The concept of hard case developed by Ronald Dworkin and Robert Alexy, as the one whose solution is not expressed in the code of laws, was adopted and argued that in cases like that the judge commonly stands before more than one decision rationally justifiable. The seven trials were typified as hard cases. A concept of popular participation was built for the research purposes, which brought together normative contributions of theoretical approaches of participatory democracy, deliberative and radical. To perform such investigation, the votes published in the trials were rated into four categories, according to the presence or absence of the citizen participation reference, if they referred to it as an argument and for what purpose: to defend ficha limpa ( clean slate ) or the independence that the court expressed in relation to it. In spite of the public participation seen in these processes, especially in the year 2008 and the following, the Supreme Court and the TSE did not stage political decisions in the analyzed trials, since they had ratified policy decisions that have been already taken by the Legislature. On the other hand, reviews of the trials revealed some votes in whose speech grounds contain a reference to popular participation in the judgments accomplished in 2010, 2011 and 2012. The main influence has been seen in the last trial, the ADC's 29 and 30 and ADI 4578, decided by the Supreme Court, where the number of votes in favor of the thesis of ficha limpa ("clean slate") filled with arguments containing references to popular participation, was higher. In this trial, ministers who used to defend the independence of the court in relation to this influence began to justify their votes in favor of "clean slate" in popular participation. Others simply left out the speech which preached that the court should be free of such interference. Therefore, remains concluded that popular participation has affected the outcome of the hard case "ficha limpa ( clean slate".